2018
DOI: 10.6061/clinics/2018/e792s
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activating factor receptor antagonists improve the efficacy of experimental chemo- and radiotherapy

Abstract: Platelet activating factor is a lipid mediator of inflammation, and in recent decades, it has emerged as an important factor in tumor outcomes. Platelet activating factor acts by specific binding to its receptor, which is present in both tumor cells and cells that infiltrate tumors. Pro-tumorigenic effects of platelet activating factor receptor in tumors includes promotion of tumor cell proliferation, production of survival signals, migration of vascular cells and formation of new vessels and stimulation of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 71 publications
0
26
0
3
Order By: Relevance
“…Our results indicate an increase in thrombin generation in breast cancer cells treated with Tamoxifen. Notably both cells lines are implicated in the secretion of Platelet Activating Factor (PAF) under thrombin stimulation, which in addition to mediating platelet aggregation, in an autocrine manner also enhances tumour progression 64,65 ; however, T47D cells appeared to induce a more hypercoagulatory environment than MCF7 cells. Tamoxifen-treated T47D cells induced later stages of platelet activation associated with a loss of CD62P IPA and persistence of CD63 IPA reflecting hypercoagulation in both PRP and WB, compared to MCF7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate an increase in thrombin generation in breast cancer cells treated with Tamoxifen. Notably both cells lines are implicated in the secretion of Platelet Activating Factor (PAF) under thrombin stimulation, which in addition to mediating platelet aggregation, in an autocrine manner also enhances tumour progression 64,65 ; however, T47D cells appeared to induce a more hypercoagulatory environment than MCF7 cells. Tamoxifen-treated T47D cells induced later stages of platelet activation associated with a loss of CD62P IPA and persistence of CD63 IPA reflecting hypercoagulation in both PRP and WB, compared to MCF7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The LOC100300716 gene is the immunoglobulin heavy variable 4-38-2 that is involved in antigen recognition and is conserved in human and other primates. The PTAFR receptor binds platelet activating factor (PAF), which has been implicated in a number of diseases and disorders like asthma, allergies and is also a lipid mediator of inflammatory responses [46]. These genes underscore the potential involvement that immune responses and inflammatory pathways seem to have with feed efficiency in the mesenteric adipose tissue.…”
Section: Genes Identified For the Gain X Intake Interactionmentioning
confidence: 99%
“…For example, RNA-seq indicated a 72-fold increase of the PTAFR gene in the A549/DDP cells. It has been reported that activated PTAFR-dependent pathways in tumor cells affect the tumor microenvironment and the phenotype of the tumor-associated macrophages to promote tumor growth 90 , 91 . Of note, we did not find any previous study on PTAFR’s regulatory effect on A549/DDP cells.…”
Section: Discussionmentioning
confidence: 99%